The role of perceived housing quality and perceived choice to recovery: An ecological perspective on a housing first program in Lisbon. (September 2016) - Martins, Paulo; Ornelas, José; Silva, Ana Cristina
Abstract: This study explores, from an ecological perspective, the relationship between perceived housing quality and the perception of choice, and between perceived choice and recovery of 45 Housing First Lisbon participants. For this purpose, we used a quantitative method and applied three instruments that report perceived housing quality, perceived choice and severe mental illness recovery. The findings reveal a significant and positive association between perceived housing quality and perceived choice, and between perceived choice and recovery, with choice being predicted by housing quality and recovery predicted by choice. These results reinforce the scientific evidence regarding the success of housing first models as a consumer choice-driven intervention, addressing pertinent environmental factors that contribute to housing stability. The study demonstrates that recovery processes can be maximized through services that empower their consumers by allowing them to choose and control the priority and order of the support services received. Highlights: We examine the relationship between perceived housing quality, perceived choice and recovery of formerly homeless persons. We find perceived housing quality predicts the perception of choice. We find perception of choice predicts recovery. Services should consider its' users' needs, towards transformative change of recovery oriented interventions. We draw upon conclusions for policy change regarding mental health services.